Cultural Diversity and Peaceful Coexistence in Islam | التنوع الثقافي والتعايش السلمي في الاسلام - Khaled Yahya Mahdaly; Mohamad Erihadiana (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
In this research, I wanted to explain the approach of Islam in the issue of cultural diversity and peaceful coexistence in societies and its impact on that, explaining the correct view of Islam and its goal that emphasizes harmony and peaceful coexistence in the presence of cultural diversity. One of the most important results of the research is that Islam believes in diversity and cultural pluralism, being a divine will that came for a very effective purpose that's only known by Allah the Almighty, and that Islam calls for the consolidation of the principle of human dignity, whatever his or her religion, gender, race, color, or belief.I divided this brief research into two topics.  In the first topic, I talked about the concept of cultural diversity and the care of Islamic legislation with practical examples, and in the second topic the concept of peaceful coexistence and its application, and the research approach that I used is the approach of desk research.